Strengthening Settlement Resilience through Local Wisdom: A Case Study of the Infrastructure and Facilities Draft Regulation in Klungkung, Bali - A A Gde Sutrisna Wijaya Putra; Heeppy Haryadi Harahap; Qanitatul Isra Qamal; Lusyana Eka Wardani; Faisal Abdullah (Syntax Literate, 2026)
Settlement resilience in Klungkung Regency faces significant challenges due to rapid housing growth (8.2% per year) that is not balanced by adequate infrastructure, facilities, and utilities (Prasarana, Sarana, dan Utilitas [PSU]). These challenges are further compounded by the absence of local regulations governing PSU handover. This qualitative study employed an embedded case study design. Data were collected through in-depth interviews with 12 key informants, including government officials, developers, village heads, customary leaders, and banjar heads, as well as through field observations using a checklist based on Government Regulation No. 12/2021 and document analysis. Data analysis utilized the interactive model of Miles, Huberman, and Saldaña, incorporating regulatory analysis, the Disaster Risk Reduction (DRR) framework, and SWOT analysis. The findings indicate that PSU conditions remain far below national standards: 75% of housing estates have damaged roads, 75% experience clogged drainage systems, 100% lack green open spaces, and 100% have PSU assets that have not yet been formally handed over. In addition, one housing estate has been abandoned due to an inactive developer. Normatively, the Rancangan Peraturan Daerah (Ranperda) aligns with national regulations and incorporates three local innovations: recognition of customary villages (Article 13), provisions regarding abandoned PSU (Article 14), and spatial planning synchronization based on Tri Angga. However, implementation still faces three major gaps: limited supervisory capacity (with a ratio of 1:15.7), low community participation (only 20% of residents understand PSU obligations), and the absence of an inventory system for abandoned PSU assets. Local wisdom values derived from Tri Hita Karana and the banjar system demonstrate strong potential to strengthen PSU management through the ngayah tradition for routine maintenance. This study integrates three frameworks—regulatory analysis, DRR, and local wisdom—and provides empirical evidence regarding the operationalization of Tri Hita Karana in PSU management.